1998
DOI: 10.1076/ceyr.17.3.251.5217
|View full text |Cite
|
Sign up to set email alerts
|

The glutathione levels are reduced in Goto-Kakizaki rat retina, but are not influenced by aminoguanidine treatment

Abstract: The results indicate that impaired glucose metabolism may influence one of the defense mechanisms for oxidative stress, but also suggest that decreased glutathione levels occur prior to morphological signs of pericyte loss and/or endothelial cell proliferation in this animal model of hereditary NIDDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…13 The contribution of glycation/glycoxidation to oxidative stress in the diabetic retina has been examined using aminoguanidine, which was found to have a protective effect against oxidative damage in models of type I 14 but not type II diabetes. 15 However, these results can not be seen as conclusive as, in addition to its capacity to react with carbonyls thereby inhibiting AGE formation, aminoguanidine can directly act as an antioxidant 16 and inhibits nitric oxide production. 17 Glycated proteins may contribute to oxidative stress in other ways as it has been observed that glycated forms of some proteins, including elastin, can chelate transition metals in a redox-active form and thus catalyse free radical generation via Fenton-type reactions.…”
Section: Oxidative Reactions Involving Glucosementioning
confidence: 95%
“…13 The contribution of glycation/glycoxidation to oxidative stress in the diabetic retina has been examined using aminoguanidine, which was found to have a protective effect against oxidative damage in models of type I 14 but not type II diabetes. 15 However, these results can not be seen as conclusive as, in addition to its capacity to react with carbonyls thereby inhibiting AGE formation, aminoguanidine can directly act as an antioxidant 16 and inhibits nitric oxide production. 17 Glycated proteins may contribute to oxidative stress in other ways as it has been observed that glycated forms of some proteins, including elastin, can chelate transition metals in a redox-active form and thus catalyse free radical generation via Fenton-type reactions.…”
Section: Oxidative Reactions Involving Glucosementioning
confidence: 95%
“…NIDDM has been studied in several animal models including the GK rat, which was selected for this study because it represents a good model of hereditary non-obese NIDDM that develops into a moderate and stable diabetic state with age [20,31]. Several reports showed that increased levels of glucose found in NIDDM patients are responsible not only Fig.…”
Section: Discussionmentioning
confidence: 99%
“…One important antioxidant is glutathione (GSH), which protects proteins against oxidative damage in the retina. 11 In various animal models of diabetes, retinal GSH levels [12][13][14][15] and the GSH/cysteine ratio 16 decrease by time, implicating that the abnormalities of retinal metabolism in diabetes result in deterioration of this antioxidant defence system. Retinal GSH levels are likely to be regulated by Müller cells, 17 and Pow and Crook 18 found immunocytochemical evidence for high levels of reduced GSH in retinal glial and as well as in horizontal cells.…”
Section: Introductionmentioning
confidence: 99%